Avaliação da capacidade funcional e nível de independência em mulheres idosas - Rosa, Icriciane Alves da; Meazzi, Rafael (My University, 2024)
Introduction: Human aging, as revealed by the World Health Organization (WHO) in 2023, is associated with an increase in life expectancy, with an estimated 77 years by 2048. Despite the gains in longevity, the process is accompanied by challenges such as functional decline and the appearance of comorbidities, highlighting the importance of evaluating functional independence and quality of life in older adults. Objective: To evaluate gait speed and the level of independence in basic activities of daily living (BADLs) in elderly women. Methodology: An observational, descriptive, quantitative, and cross-sectional study. Nine elderly women, with a mean age of 70.11 (±4.65) years, were evaluated. Independence in ADLs was assessed using the Modified Barthel Index (MB). The evaluation of global functional capacity was performed using the 6-Minute Walk Test (6MWT), calculating the kinematic parameters of gait. The data were analyzed using the IBM® SPSS® Statistics v.21 program. Results: The mean gait speed was 1.08 (±0.21) meters per second; step cadence, 114.00 (±10.00) steps per minute; step length, 0.53 (±0.05) meters; percent support phase, 62.44 (±2.94) percent. The BI score was altered in 55.6% of the subjects evaluated. Conclusion: A significant correlation was found between the kinematic aspects of gait. However, when relating gait speed to age and the BI score, no significant differences were found. [resumo fornecido pelos autores]
Introdução: O envelhecimento humano, conforme revelado pela Organização Mundial da Saúde (OMS) em 2023, está associado ao aumento da expectativa de vida, prevendo-se alcançar 77 anos até 2048. Apesar dos ganhos na longevidade, o processo é acompanhado por desafios como declínio funcional e aparecimento de comorbidades, destacando a importância de avaliações da independência funcional e qualidade de vida em idosos. Objetivo: Avaliar a velocidade da marcha e o nível de independência em atividades básicas de vida diária em mulheres idosas. Metodologia: Estudo observacional, descritivo, quantitativo e de corte transversal. Foram avaliadas nove mulheres idosas, com idade média de 70,11 (±4,65) anos. A independência nas atividades de vida diária (AVDs) foi avaliada usando o Índice de Barthel Modificado (IB). A avaliação da capacidade funcional global foi realizada através do Teste de Caminhada de 6 Minutos (TC6M), calculando-se os parâmetros cinemáticos da marcha. Os dados foram analisados pelo programa IBM® SPSS® Statistics v.21. Resultados: A velocidade média da marcha foi de 1,08 (±0,21) metros por segundo; cadência do passo, 114,00 (±10,00) passos por minuto; comprimento do passo, 0,53 (±0,05) metros; percentual da fase de apoio, 62,44 (±2,94) por cento. O resultado do IB foi alterado em 55,6% das avaliadas. Conclusão: Foi encontrada correlação significativa entre os aspectos cinemáticos da marcha. Porém, ao relacionar a velocidade da marcha com idade e score gerado pelo IB, não foram encontradas diferenças significativas. [resumo fornecido pelos autores]
Keywords: Fisioterapia; Marcha; Idosas; Envelhecimento; Caminhada - Testes